Long-term Outcomes of Balloon Dilation for Persistent Eustachian Tube Dysfunction. Issue 10 (December 2019) - Cutler, Jeffrey L.; Meyer, Ted A.; Nguyen, Shaun A.; O'Malley, Ellen M.; Thackeray, Lisa; Slater, Patrick W.
Abstract : Objective: To gather long-term follow-up data on the efficacy of balloon dilation for treating patients with persistent Eustachian tube dysfunction (ETD). Study Design: Extended follow-up study of the treatment arm of a prospective, multicenter, randomized controlled trial. Setting: Tertiary care academic center and private practice. Patients: Patients diagnosed with medically refractory persistent ETD. Interventions: Balloon dilation of the Eustachian tube. Main Outcome Measures: The endpoints were the mean change from baseline in the 7-item Eustachian Tube Dysfunction Questionnaire (ETDQ-7) score, revision dilation rate, changes in assessments of middle ear function, and patient satisfaction. Results: A total of 47 participants enrolled in the extended follow-up study. Mean follow-up was 29.4 months (range, 18–42 mo). There was a statistically significant mean (SD) change from baseline in the overall ETDQ-7 score (–2.5 ± 1.2; p  < 0.0001). A reduction of one or more in their overall ETDQ-7 score was observed by 93.6% (44/47) participants. The revision dilation rate was 2.1% (1/47). Among participants with abnormal baseline middle ear assessments, 76.0% had normalized tympanic membrane position ( p  < 0.0001), 62.5% had normalization of tympanogram type ( p  < 0.001), and 66.7% had positive Valsalva maneuvers ( p  < 0.0001). Participant satisfaction was 83.0% at long-term follow-up. Conclusions: Balloon dilation results in durable improvements in symptoms and middle ear assessments for patients with persistent Eustachian tube dysfunction at mean follow-up of longer than 2 years.